ТЕОРЕТИЧНІ ОСНОВИ ОРГАНІЗАЦІЇ ІНВАРІАНТНИХ ПЕРЕТВОРЮВАЛЬНИХ СИСТЕМ АВТОНОМНИХ ОБ’ЄКТІВ - Смирнов, В.С.; Самков, О.В.; Штіфзон, О.Й.; Любицький, С.В.; Лізанець, В.В. (Інститут електродинаміки Національної академії наук України, 2017)
A development of the theory of invariant conversion system construction with a multiple modulation was considered. Based on the theoretical studies, a provision on the structural invariance of conversion systems was represented. The positions of a hypercomplex analysis of conversion systems with a multiple modulation are proposed. A position of quadruplex transformation was developed. The principles of organization and control algorithms of multi-functional converters with multiple modulation were substantiated. References 7, figures 4, tables 3.